Respuesta :

loveuV

Answer:

[tex]n=\frac{189}{104}[/tex]

Step-by-step explanation:

7−2(8n−3)=4(n−2)(22)

Step 1: Simplify both sides of the equation.

7−2(8n−3)=4(n−2)(22)

7+(−2)(8n)+(−2)(−3)=88n+−176(Distribute)

7+−16n+6=88n+−176

(−16n)+(7+6)=88n−176(Combine Like Terms)

−16n+13=88n−176

−16n+13=88n−176

Step 2: Subtract 88n from both sides.

−16n+13−88n=88n−176−88n

−104n+13=−176

Step 3: Subtract 13 from both sides.

−104n+13−13=−176−13

−104n=−189

Step 4: Divide both sides by -104.

[tex]-\frac{104n}{104} =-\frac{189}{104} \\n=\frac{189}{104}[/tex]

Answer:

[tex]n=\frac{189}{104} \\[/tex]

Hope this helps

ACCESS MORE